Review of the leafhopper genus Stirellus Osborn & Ball, 1902 (Hemiptera: Cicadellidae: Deltocephalinae) with description of two new species from Pakistan - Naveed, Hassan; Shah, Bismillah; Sohail, Kamran; Zhang, Yalin (Zootaxa, 2020)
The genus Stirellus Osborn & Ball is revised for Pakistan. Four species are included, of which two are new. S. kumratensis sp. nov. and S. neoconvexus sp. nov. are described and illustrated. A key to all species of this genus from Pakistan is provided.